2022
DOI: 10.1002/zoo.21677
|View full text |Cite
|
Sign up to set email alerts
|

Differing animal welfare conceptions and what they mean for the future of zoos and aquariums, insights from an animal welfare audit

Abstract: Animal welfare is a growing public concern that has the potential to undermine the social license of zoos and aquariums. The lack of consensus on how animal welfare is defined across such a diverse sector combined with and a widespread belief that commercial priorities such as entertaining visitors conflicts with animal welfare, hinders efforts to effectively address this fundamental issue for the sector. Data derived from an audit of habitats across a major North American wildlife attraction revealed that hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…There is also strong consensus that welfare assessments should include resource (i.e., input)‐ and animal‐based (i.e., output) metrics (NASEM, 2020; Sherwen et al, 2018), with some individuals and regulatory authorities advocating a shift towards mostly or exclusively considering animal‐based metrics (e.g., EFSA, 2012; Gonyou, 1993). This shift is consistent with other calls for animal welfare management to shift focus to animal feelings (e.g., Veasey, 2022). Finally, documenting and tracking of assessments is an essential element.…”
Section: Is Anything Measurable and Comparable Across Ungulate Manage...supporting
confidence: 89%
See 2 more Smart Citations
“…There is also strong consensus that welfare assessments should include resource (i.e., input)‐ and animal‐based (i.e., output) metrics (NASEM, 2020; Sherwen et al, 2018), with some individuals and regulatory authorities advocating a shift towards mostly or exclusively considering animal‐based metrics (e.g., EFSA, 2012; Gonyou, 1993). This shift is consistent with other calls for animal welfare management to shift focus to animal feelings (e.g., Veasey, 2022). Finally, documenting and tracking of assessments is an essential element.…”
Section: Is Anything Measurable and Comparable Across Ungulate Manage...supporting
confidence: 89%
“…Welfare assessments that consider different approaches to welfare (e.g. biological functioning, natural behaviors, affective states ;Fraser, 2008;Hemsworth et al, 2015), both positive and negative experiences, both resource-based inputs (e.g., nutritionally balanced diets, appropriate social groupings, and professional veterinary care) and animal-based outputs (e.g., expression of behavior indicating positive states like play, bonding behaviors, minimal, or no experience of pain; Veasey, 2017), represent current thinking in animal welfare science (NASEM, 2020), though it has been argued that outputs (Gonyou, 1993), and affective states (Duncan, 2004;Petersen & Ryberg, 2014;Veasey, 2017Veasey, , 2022 are perhaps most relevant since they measure how the animal is faring in the environment provided and/or its subjective experience (but see Robbins et al, 2018). The Five Domains model (Mellor, 2017) of animal welfare is currently one of the most widely referenced models of animal welfare and has been adopted by the World Association of Zoos and Aquariums (Mellor et al, 2015) and suggested by the AZA as an approach for assessing animal welfare.…”
Section: Welfare Assessment Across the Zoo To Large Landscape Continuummentioning
confidence: 99%
See 1 more Smart Citation
“…The similarities and difference in beliefs and perceptions of truth presented in this paper form a useful basis for future cooperation and learning, and may go some way to explaining the similarities and differences in zoo husbandry and conservation activities around the world. Increasingly, cooperation and educational activities to support good zoo animal welfare are being developed (e.g., de Mori et al, 2019;Kagan et al, 2015;Walraven & Duffy, 2017) but as demonstrated in this paper, differences in perceptions and standards of zoo animal welfare exist (Veasey, 2022;Ward et al, 2020) and in order for education to be effective, it is important that it is relevant to the pre-existing beliefs of the target audience (Brown, 2009;Stringer et al, 2011Stringer et al, , 2018.…”
Section: Notementioning
confidence: 96%
“…Animal welfare in commercial and entertainment sectors is often viewed within the contexts of profitability, feasibility, and ethics, with the understanding that welfare considerations may differ between those taking care of the animals and those being entertained by the animals (Veasey, 2022). Understanding pain in animals is important for ethical reasons, and animal welfare policy implementation can aid in instilling public trust in science as well as protecting animals in commercial and entertainment sectors.…”
Section: Animal Care Implicationsmentioning
confidence: 99%